Medical Tourism Masyarakat Indonesia Ke Malaysia : Fenomena Tindakan Kesehatan Di Tahun 2000-2020 - Nurul Azizah; Imas Emalia; Lili Sudria Wenny (PURBAWIDYA, 2026)
This article examines the phenomenon of medical tourism among Indonesians to Malaysia for health care from 2000 to 2020. This paper aims to analyze the reasons why Indonesians choose Malaysia as a medical destination. It also aims to analyze medical practices shaped within the social, cultural, and regional health system contexts. The method used is a historical method to reconstruct past medical tourism practices between 2000-2020. The sociological approach to health utilizes Talcott Parsons' action systems theory. In the theory of social action, individual and group actions result from interactions among goals, means, norms, and conditions within the cultural, social, and personality systems of humans. This paper reveals that the medical tourism actions of Indonesian people to Malaysia include both personal and group actions that are structured and repetitive. In terms of social means, medical treatment in Malaysia is influenced by easy access to information integrated into the health system, the Malaysian tourism industry, which is a source of knowledge, norms, culture, and other social systems. Since the early 2000s, medical tourism has developed in Malaysia, which has then become a major destination for people in Southeast Asia, including Indonesia. These medical tourists practically chose their visit due to geographical proximity to their homes. However, this was also due to the assumption of satisfaction with healthcare services and the success rate of treatment from Malaysia's healthcare system, whether modern, traditional, or a combination of both. The analysis in this paper shows that medical tourism by Indonesians to Malaysia from 2000 to 2020 was a health action realized by individuals and social groups after gaining knowledge about the healthcare system, cultural norms, and interactions between the two parties, namely the Indonesian and Malaysian communities.